PENGGUNAAN SISTEM INFORMASI DALAM KOMUNIKASI BISNIS SECARA ELEKTRONIK - Mari Rahmawati (Jurnal Komunikasi, 2017)
Abstract-A comparison between traditional trade and electronic commerce can be used to improve the sales system. In this case, we can see that electronic commerce not only simplifies the delivery of information and goods or services, but it can also change their relationships. Visitors on the website can do more than see the information, they can either e-mail or fill out a form, and make agreements that are more than just a traditional agreement. E-commerce allows us to sell products and services online. Prospective customers or consumers can find your website, read and view the products, order and pay for those products online. Electronic commerce or e-commerce is the dissemination, purchase, sale, marketing of goods and services through electronic systems such as internet or television, www, or other computer networks. E-commerce can involve the transfer of electronic funds, electronic data exchange, automated inventory management systems, and automated data collection systems.